Acupuncture in management of acute dental pain - A systematic review and meta-analysis - Moritz Müller; Christine Schmucker; Johannes Naumann; Nadine Schlueter; Roman Huber; Ann-Kathrin Lederer (Elsevier, 2023)
Acute dental pain is a common issue leading to dental consultation. Besides causal therapy, patients are treated with acupuncture, but efficacy in acute dental pain is still not clarified. We aimed to evaluate results of recent research to estimate the efficacy of acupuncture compared to pain-relieving approaches in treatment of acute dental pain. A systematic review of controlled trials being published between database inception and 2020 were conducted to evaluate the efficacy of acupuncture (alone or as complementary therapy) compared to local anesthesia or conventional analgesic medications in acute dental pain (intraoperatively and postoperatively) and to clarify whether acupuncture reduces the use of postoperative analgesic medications. Of 1672 publications, 23 publications met the inclusion criteria. From these, 11 randomized controlled trials (n = 668) reported on the efficacy of acupuncture on postoperative acute dental pain. Patients, who received acupuncture, showed lower pain scores postoperatively compared to sham acupuncture (Relative Risk −0.77, 95% Confidence interval −1.52 to −0.03). Overall, the results suggest a potential role of acupuncture in improving acute dental pain intraoperatively and postoperatively as well as improving the efficacy of local anesthesia, but the results are limited due to methodological shortcomings emphasizing the necessity for future high-quality research.